2018
DOI: 10.1055/s-0038-1668519
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Safety of the Zygomatic Osteotomy in Middle Cranial Fossa Surgery: A Retrospective Cohort Review

Abstract: Background Zygomatic osteotomy, an adjunct to middle cranial fossa (MCF) surgical approaches, improves the superior-inferior angle of approach and minimizes temporal lobe retraction. However, a decision-making algorithm for selective use of the zygomatic osteotomy and the impact of the zygomatic osteotomy on surgical complications have not been well documented. Objective We described an algorithm for deciding whether to use a zygomatic osteotomy in MCF surgery and evaluated complications associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For that reason, it seems that the effectiveness of the zygomatic arch osteotomy for the STA-SCA bypass, which does not contribute to minor-axis length, is limited. Moreover, since zygomatic arch osteotomy has been reported to cause complications including facial nerve palsy, trismus, sensory disturbance in the trigeminal nerve territory, and masseter muscle atrophy, its use must be carefully considered [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, it seems that the effectiveness of the zygomatic arch osteotomy for the STA-SCA bypass, which does not contribute to minor-axis length, is limited. Moreover, since zygomatic arch osteotomy has been reported to cause complications including facial nerve palsy, trismus, sensory disturbance in the trigeminal nerve territory, and masseter muscle atrophy, its use must be carefully considered [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the paper entitled "Indications and Safety of the Zygomatic Osteotomy in Middle Cranial Fossa Surgery: A Retrospective Cohort Review" by Neal et al 1 The authors concluded that "zygomatic osteotomy (ZO) was preferentially used because of the increased exposure of the surgical window needed to resect these larger tumors," "did not increase the risk of surgery as measured by incidence of surgical complications," and "increase the operative window, facilitate multidirectional access, and decrease temporal lobe retraction." However, several studies reported no significant differences in terms of surgical exposure.…”
mentioning
confidence: 99%